2023
DOI: 10.3748/wjg.v29.i16.2397
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 induced liver injury: Incidence, risk factors, impact on COVID-19 severity and prognosis in different population groups

Abstract: Liver is unlikely the key organ driving mortality in coronavirus disease 2019 (COVID-19) however, liver function tests (LFTs) abnormalities are widely observed mostly in moderate and severe cases. According to this review, the overall prevalence of abnormal LFTs in COVID-19 patients ranges from 2.5% to 96.8% worldwide. The geographical variability in the prevalence of underlying diseases is the determinant for the observed discrepancies between East and West. Multifactorial mechanisms are implicated in COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 325 publications
(461 reference statements)
0
5
0
Order By: Relevance
“…Liver injury was the most frequently described extrapulmonary manifestation (17.28%) in our study group, as presented in Table 1. The data on liver injury in COVID-19 patients are heterogeneous [1]-a systematic review indicated mild liver function in every fourth to fifth patient [25]. In our analyses, liver injury was associated with obesity and therapy (corticosteroids, anakinra, favipiravir, and remdesivir), while the highest OR was associated with the Delta wave, as presented in Table 5.…”
Section: Extrapulmonary Manifestations Liver Injurymentioning
confidence: 66%
See 1 more Smart Citation
“…Liver injury was the most frequently described extrapulmonary manifestation (17.28%) in our study group, as presented in Table 1. The data on liver injury in COVID-19 patients are heterogeneous [1]-a systematic review indicated mild liver function in every fourth to fifth patient [25]. In our analyses, liver injury was associated with obesity and therapy (corticosteroids, anakinra, favipiravir, and remdesivir), while the highest OR was associated with the Delta wave, as presented in Table 5.…”
Section: Extrapulmonary Manifestations Liver Injurymentioning
confidence: 66%
“…The pulmonary manifestations of COVID-19 are well recognized, but COVID-19 is associated with deleterious effects on many other organ systems. The liver is the second most common organ affected after the lung [1]. While it is now widely established that acute kidney injury (AKI) is an important complication of SARS-CoV-2 infection, there is marked variability in its reported incidence.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 death predictors have been extensively evaluated in large databases all over the world, with age being the most important factor along with male sex, number of preexisting diseases, and many comorbidities like cardiovascular and/or cerebrovascular, obesity, diabetes, and dementia [ 11 , 38 , 39 , 40 , 41 , 42 ]. Fortunately, even in immunocompromised patients, SARS-CoV-2 infection severity was much lower in the Omicron wave compared with the previous waves, as demonstrated by the WHO ISARIC UK prospective cohort study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low albumin is a marker of severity and poor outcomes [ 9 ]. The incidence of acute or acute-on-chronic liver failure (ACLF) in COVID-19 patients with chronic liver disease (CLD) was widely reported (10% to 50%), with a high mortality rate of up to 65% [ 10 , 11 , 12 ]. Patients with a SARS-CoV-2 infection may develop hepatic manifestations due to direct viral action, drug-induced liver injury (DILI), hyperinflammation, the hypoxic-ischemic mechanism [ 12 , 13 ], or exacerbation of associated liver disease; yet, it has not been possible to separate the impact of each mechanism [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, chronic hepatitis C (HCV) patients with COVID-19 are more prone to hospitalization but not at a higher risk of death. [ 46 ] The results of a comprehensive meta-analysis by Hariyanto et al [ 47 ] have also shown an association of viral hepatitis with severe COVID-19. COVID-19 can reactivate or cause a sudden increase in HBV DNA levels in the blood, hepatitis failure, and flare of acute hepatitis in patients with chronic HBV.…”
Section: Impact Of Covid-19 On Patients With Pre-existing Liver Disor...mentioning
confidence: 99%